Compact flat monopole antenna for small aircraft of VHF communication system - Wongsakulphasatch, P.; Phongcharoenpanich, C.; Kawdungta, S. (My University, 2012)
This paper presents the design of compact flat monopole antenna for the small aircraft of VHF communication system. It can operate along the wide frequency band without the matching circuit that make itself compact size. From the simulation results, the proposed antenna has a frequency range between 112 and 130 MHz. It yields an omnidirectional pattern with a linear polarization. The simulated gain is 1.88 dBi. The prototype antenna was fabricated and tested with the VHF aircraft communication system. It has sufficient characteristics for the VHF communication system. It is found that this antenna can be efficiently used for the small aircraft. © 2012 IEEE.
Keywords: Flat monopole antenna; small aircraft; VHF communication